Digital Currency Governance and Global Risk Management: Implications for World Economic Stability - Supriadi, Edi (Dinasti International Journal of Economics, Finance & Accounting, 2025)
The rapid rise of digital currencies, including cryptocurrencies and Central Bank Digital Currencies (CBDCs), creates both strategic opportunities and systemic risks for the global economy. This study investigates the impact of digital currency adoption on financial stability, with a particular emphasis on the moderating role of governance quality. Using panel data from 70 countries between 2015 and 2024, we apply Fixed Effects (FE) and System Generalized Method of Moments (System GMM) to capture the dynamic relationship between digital currency adoption, governance, and financial stability. The findings confirm that digital currency adoption significantly increases financial volatility, especially in economies with weaker governance structures. However, robust governance—characterized by effective regulation, rule of law, and cybersecurity readiness—reduces these risks and strengthens financial resilience. Furthermore, the results highlight that developing countries are more vulnerable to destabilizing effects compared to developed nations, underscoring the urgent need for international support and harmonized global standards. This study contributes to the literature by providing empirical evidence on the governance–stability nexus in the era of financial digitalization and offers concrete policy implications for regulators and international organizations.